2023
DOI: 10.1136/bmjopen-2022-066967
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative exploration of melanoma awareness in black people in the USA

Abstract: ObjectiveAlthough black patients are more likely to have advanced melanomas at diagnosis, with a 5-year survival rate among black patients of 70% compared with 92% for white patients, black people are generally not the focus of melanoma public health campaigns. We sought to explore awareness and perspectives of melanoma among black people to inform the development of relevant and valued public health messages to promote early detection of melanoma.DesignInductive thematic analysis of in-depth semistructured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Similarly, a review demonstrated that 100% of skin cancers depicted on SM advertisements had a background of Fitzpatrick type I or II skin [ 54 ]. SM representation is critical, as a study that interviewed 27 African American individuals found SM to be a primary means by which people with darker pigmentation are exposed to public health messages related to skin cancer [ 55 ]. Participants also stated it would be important for skin cancer awareness messages on SM to feature Black communities to feel that the information is relevant to them [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a review demonstrated that 100% of skin cancers depicted on SM advertisements had a background of Fitzpatrick type I or II skin [ 54 ]. SM representation is critical, as a study that interviewed 27 African American individuals found SM to be a primary means by which people with darker pigmentation are exposed to public health messages related to skin cancer [ 55 ]. Participants also stated it would be important for skin cancer awareness messages on SM to feature Black communities to feel that the information is relevant to them [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…The reason for this disparity is multifactorial. Contributing factors include a higher proportion of acral lentiginous melanoma, which is more aggressive than other types of melanoma; lack of patient education regarding melanoma; lack of clinician awareness; and disparities in access to medical care …”
Section: Melanoma In Racial and Ethnic Minority Groupsmentioning
confidence: 99%
“…In general, public health campaigns do not effectively incorporate messages for Black individuals. As a result, awareness of the possibility of developing melanoma may be very low . Along with important and widely disseminated UV-focused skin cancer prevention messages aimed at fair-skinned individuals, messages should be specifically tailored to reflect the nuance and specifics of the presentation of melanoma in Black individuals.…”
Section: Tailored Public Health Messaging For Early Detection Of Mela...mentioning
confidence: 99%
See 2 more Smart Citations